If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1000 = (30 + x)(15 + x) Multiply (30 + x) * (15 + x) 1000 = (30(15 + x) + x(15 + x)) 1000 = ((15 * 30 + x * 30) + x(15 + x)) 1000 = ((450 + 30x) + x(15 + x)) 1000 = (450 + 30x + (15 * x + x * x)) 1000 = (450 + 30x + (15x + x2)) Combine like terms: 30x + 15x = 45x 1000 = (450 + 45x + x2) Solving 1000 = 450 + 45x + x2 Solving for variable 'x'. Combine like terms: 1000 + -450 = 550 550 + -45x + -1x2 = 450 + 45x + x2 + -450 + -45x + -1x2 Reorder the terms: 550 + -45x + -1x2 = 450 + -450 + 45x + -45x + x2 + -1x2 Combine like terms: 450 + -450 = 0 550 + -45x + -1x2 = 0 + 45x + -45x + x2 + -1x2 550 + -45x + -1x2 = 45x + -45x + x2 + -1x2 Combine like terms: 45x + -45x = 0 550 + -45x + -1x2 = 0 + x2 + -1x2 550 + -45x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 550 + -45x + -1x2 = 0 Factor a trinomial. (10 + -1x)(55 + x) = 0Subproblem 1
Set the factor '(10 + -1x)' equal to zero and attempt to solve: Simplifying 10 + -1x = 0 Solving 10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10Subproblem 2
Set the factor '(55 + x)' equal to zero and attempt to solve: Simplifying 55 + x = 0 Solving 55 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + -55 + x = 0 + -55 Combine like terms: 55 + -55 = 0 0 + x = 0 + -55 x = 0 + -55 Combine like terms: 0 + -55 = -55 x = -55 Simplifying x = -55Solution
x = {10, -55}
| 14-2x+4x=72 | | 10=-5(x-5) | | 2r-(5+-r)=13+2r | | 3x-(x+1)=-2+5(x-4) | | 0.9x=.2 | | =x^4-6x^2+9 | | -33=16x+15 | | (x+10)=360 | | [4x-8]-3x=6x+2 | | 8x+22+9=19 | | .2(60)+0.05=.1(60+x) | | 1.3x+2.8=3.2x-1 | | 22=x+2+10 | | (4-w)=3(2w+2) | | 8-abs(1-3x)=-1 | | 2x^2+7=7x | | 22=22+2+10 | | 75=-5[4x+1] | | -1x=4x-3 | | 5z(z-2)+3z(z+4)= | | 7n+7=5(-5-5n) | | 22=2+10 | | 3x+18+12x-9=5x-2 | | 6y+9=3(2y-3) | | X^4-3x^3-12x^2=0 | | 6(5x+4)+3(2x+6)+5=36x+48 | | -0.87y+2=y-0.6 | | -40=-8(8-m) | | -6(x-9)=-42 | | 7+8(4+4x)=6x-39 | | -8a+6a+42=1 | | 4x-3(x-1)=-4+3x+11 |